2017
DOI: 10.5194/nhess-2017-176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of shallow landslide susceptibility using an artificial neural network in Enshi region, China

Abstract: 17Landslides are one of the most common and damaging natural hazards in mountainous areas. 18 However, due to the complex mechanisms that influence the activation of landslides, it can often be 19 very difficult to predict exactly when a landslide will occur. Therefore, research on landslide Nat. Hazards Earth Syst. Sci. Discuss.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…According to the research, the frequency vibrations caused by cars on highways in turn cause landslides [104]. Many researchers have reported that roads along slope imbalance in study areas are the most influential anthropogenic factor [31,40,57,63,74,75,92,[105][106][107][108][109][110]…”
Section: Relationship With Anthropologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the research, the frequency vibrations caused by cars on highways in turn cause landslides [104]. Many researchers have reported that roads along slope imbalance in study areas are the most influential anthropogenic factor [31,40,57,63,74,75,92,[105][106][107][108][109][110]…”
Section: Relationship With Anthropologymentioning
confidence: 99%
“…In this manner, the slope change causes landslides [2,40,69]. Zeng et al [110] reported that landslides in the Enshi region occurred at slopes whose slope changed during road construction.…”
Section: Relationship With Load Changementioning
confidence: 99%
“…The study of neural networks began in the 40s of last century, mainly focused on the physiology and psychology of brain function, and the electrophysiological aspects of neurons [10]. American psychologist Mika Rocco and mathematician Peters jointly established the mathematical model of formal neurons in 1943, which laid the foundation of neuroscience theory research [11]. In the following 20 years, many scientists have studied this theory from different angles, such as neuronal link strength, artificial intelligence, neural networks and so on, and obtained many important research results [12].…”
Section: A the Principle Of Artificial Neural Networkmentioning
confidence: 99%
“…Therefore, research on landslide prevention and mitigation mainly focuses on the distribution forecasting of unstable slopes that are prone to landslides in specific regions and under multiple external forces (Zeng et al, 2017). The prediction of the spatial distribution of unstable slopes, termed landslide susceptibility zonation, is important in assistance with government land-use planning and in reducing unnecessary loss of life and property.…”
Section: ключові слова: ґрунтові води прогноз рівень гідродинамічнmentioning
confidence: 99%